2010
DOI: 10.5483/bmbrep.2010.43.1.040
|View full text |Cite
|
Sign up to set email alerts
|

Transduced PEP-1-AMPK inhibits the LPS-induced expression of COX-2 and iNOS in Raw264.7 cells

Abstract: AMP-activated protein kinase (AMPK) is a heterotrimeric

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…In the tube formation assay of HUVEC cells, both total tube length and the number of branching points were increased in the FFA treatment group compared to the control group and cell proliferation was not significantly affected at the time when tube formation assay was performed. AMP-activated protein kinase (AMPK) is a key regulator of metabolic homeostasis (35) and has anti-inflammatory effects (37,38). In addition, it promotes angiogenesis, and protects cells from apoptosis (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…In the tube formation assay of HUVEC cells, both total tube length and the number of branching points were increased in the FFA treatment group compared to the control group and cell proliferation was not significantly affected at the time when tube formation assay was performed. AMP-activated protein kinase (AMPK) is a key regulator of metabolic homeostasis (35) and has anti-inflammatory effects (37,38). In addition, it promotes angiogenesis, and protects cells from apoptosis (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…Activation of AMPK also underlies the anti-inflammatory actions of FFA (Pilon et al, 2004;Cheng et al, 2007;Jeong et al, 2009;Aoki et al, 2010;Cai et al, 2010;Shin et al, 2010). A series of studies demonstrated that AMPK mediates the anti-inflammatory effects of a variety of agents, including nicotine, berberine, cilostazol, and adiponectin (Pilon et al, 2004;Cheng et al, 2007;Jeong et al, 2009;Aoki et al, 2010;Cai et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…First, AMPK can be activated by Ca 2ϩ through the CaMKK␤ pathway (Stahmann et al, 2006). Second, similar to FFA, AMPK has both anti-inflammatory and channel-regulatory activity (Pilon et al, 2004;Carattino et al, 2005;Cheng et al, 2007;Mace et al, 2008;Jeong et al, 2009;Klein et al, 2009;Kongsuphol et al, 2009;Kréneisz et al, 2009;Aoki et al, 2010;Cai et al, 2010;Shin et al, 2010). For example, both FFA and AMPK have been reported to suppress the inflammatory mediator-induced expression of inducible nitric-oxide synthase (iNOS) (Paik et al, 2000;Aoki et al, 2010) and inhibit sodium channel (Carattino et al, 2005;Yau et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the transduction mechanism remains unclear, PTD fusion proteins have been used to deliver therapeutic proteins in vitro and in vivo. We have shown previously that various PTD fusion proteins transduced into neuronal cells cross the blood-brain barrier and efficiently protect against cell death (14)(15)(16)(17)(18)(19)(20). In this study, we investigated the protective effects of PEP-1-p18 against MPP + -induced dopaminergic neuronal cell death and MPTP-induced PD mouse models.…”
Section: Introductionmentioning
confidence: 99%